A novel CACD/CAD/CAE integrated design framework for fiber-reinforced plastic parts. (September 2015) - Liu, Jikai; Ma, Yongsheng; Fu, Junyu; Duke, Kajsa
Highlights: Presents a CACD/CAD/CAE integrated design framework for fiber-reinforced plastic parts. Develops the heterogeneous feature model for fiber-reinforced object modeling. Develops the level-set structure and material optimization for conceptual design. Applies the response surface method to optimize the injection molding process conditions. Improves the design optimality and shortens the design process. Abstract: This work presents a novel CACD/CAD/CAE integrated framework for design, modeling, and optimization of fiber-reinforced plastic parts, which can greatly enhance the current design practice by realizing partial automation and multi-stage optimization. To support this framework, a new heterogeneous feature model (HFM) has been developed to model the fiber-reinforced objects and to be transferred between engineering modules. To be specific, the CACD (computer-aided conceptual design) module employs the level-set structure and material optimization to produce the initial design with thickness control, and also the initial HFM; the CAD (computer-aided design) module allows manual editing on the HFM to reflect various design intents; then, the injection molding CAE (computer-aided engineering) simulates the manufacturing process, and the response surface method (RSM) is applied to optimize the process parameters of gate location, injection flow rate, mold temperature and melt temperature, to approach the manufactured fiber orientation distribution close to the optimized result produced by the CACD module; besides, the structural analysis CAE module generates the mechanical performance result to support the CACD module, as well as to validate the final design. By applying this framework, the final structural design including the fiber orientation distribution, will perform better in mechanical properties, and consume less matrix and fiber materials; besides, the design maturity can be approached in shorter time. To prove the effectiveness, a plastic gripper design will be comprehensively studied.